2015
DOI: 10.1016/j.rpped.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Inatividade física e medidas antropométricas em escolares de Paranavaí, Paraná, Brasil

Abstract: OBJECTIVE: To investigate the association between physical inactivity and anthropometric measures in schoolchildren from Paranavaí-Parana, Brazil. METHODS: Cross-sectional survey, carried out in July and August 2013. Sample of 566 students (287 boys and 279 girls) from 6th to 9th grade, aged 10 to 14 years, from public and private schools of Paranavaí - PR, Southern Brazil. The variables analyzed were: time of weekly physical activity through a questionnaire (physical inactivity <300 minutes/week), body mass i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
1
19
2
4
Order By: Relevance
“…A study describing adolescents’ physical activity levels with data from 32 countries concluded that the majority of adolescents do not meet current recommendations of physical activity 4. In Brazil, high levels of physical inactivity in children and adolescents were reported in the southern5 and northeast regions 6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study describing adolescents’ physical activity levels with data from 32 countries concluded that the majority of adolescents do not meet current recommendations of physical activity 4. In Brazil, high levels of physical inactivity in children and adolescents were reported in the southern5 and northeast regions 6…”
Section: Introductionmentioning
confidence: 99%
“…Some previous Brazilian studies involving physical inactivity and sedentary behaviour focused on investigating adolescents5 , 6 but did not stratify subgroups i.e. age and gender comparisons as recommended elsewhere 7.…”
Section: Introductionmentioning
confidence: 99%
“…Quando crianças foram avaliadas pelo parâmetro CC no Canadá e no Brasil, observou-se que o percentual de crianças que apresentaram CC elevada indicou aumento de risco cardiovascular em ambos os sexos, porém, foi mais prevalente no sexo masculino (19)(20)(21) . As médias de CC encontradas no presente estudo foram também significativamente superiores no sexo masculino, resultados similares ao encontrados por outros estudos (22,23) .…”
Section: Discussionunclassified
“…No presente estudo, a prevalência da PAS e PAD com valores acima do normal foi de 12,8% e 5,9%, respectivamente, índices inferiores aos encontrados por um estudo que apresentou 45% de elevação para PAD e 29% de elevação para PAS (27) , e superior a outro estudo no qual a prevalência foi de 4 % para PAS e 3% para PAD (28) . Estudos demonstraram que as médias de PAS e PAD foram superiores no sexo masculino (20,29) , assim como o atual estudo.…”
Section: Discussionunclassified
“…According to the World Health Organization, physical activity is any body movement produced by skeletal muscles that requires energy expenditure, such as walking, cycling, and playing sports, and physical inactivity is identified as the fourth risk factor for global mortality 13 . Physical inactivity in schoolchildren is a determining factor for overweight; thus, access to physical activity is regarded as a health strategy to control obesity, which is currently considered a global public health problem 14,15 . The most active children improve their cardiorespiratory and muscle strength capacity and reduce symptoms of anxiety and depression 16 .…”
Section: Introductionmentioning
confidence: 99%